The Portuguese eremitical Congregation of the Serra de Ossa: spatial analysis of the monastic settlements - Volzone, R.; Fontes, J. L. (Journal of Medieval Iberian Studies, 2020)
The Portuguese Eremitical Congregation of São Paulo in Serra de Ossa was founded in 1482, combining a large number of eremitical settlements – documented since 1366, mostly in the Alentejo region – under a centralized government. In 1578, an autonomous congregation was set up, and became then aﬃliated with the Hungarian Order of Saint Paul the First Hermit. Their settlements were turned into monasteries, most of them only extinct due to the decree of dissolution of the religious orders in 1834. This article attempts to ﬁll in the gaps found in the material study of the Congregation’s settlements; the authors have carried out an examination of the seventeen examples – sometimes just traces – through a literature review, an archival dataset, on-site morphological and spatial analyses, with a focus on two case studies: Santa Cruz de Rio Mourinho and Nossa Senhora da Consolação de Alferrara. This preliminary survey shows continuities in the communities’ choices of location, the strategy of occupation, the architectural morphology features. The study aims to contribute to the diﬀusion of information about this monastic network, and to the creation of protective policies in relation to this cultural heritage, since all these monasteries have lost their original function and values.